Vietnamese Teachers’ Perspectives of the Impact of Reflection-on-action Teaching on Educational Quality: A Grounded Theory Study (Journal of Contemporary Educational Policies and Practices, 2023)
In the midst of Vietnam’s surge towards English bilingualism and traditional teacher-centric methodologies, the uncharted territory of on-action reflective teaching among English as a foreign language (EFL) teachers emerges as a potential avenue for enhancing pedagogical efficacy and holistic student development. This study delves into the qualitative examination of on-action reflective teaching among EFL teachers in Vietnam, a vital element of professional teaching that has not been adequately explored within the Vietnamese setting. The study is anchored on the model of reflective practice and the ecological systems theory, probing into the manner in which teachers involve themselves in on-action reflection and its subsequent impact on the caliber of teaching and learning. The data was gathered by means of semi-structured interviews with 15 teachers who teach English across various academic levels. The thematic analysis showed that the teachers participated in both individual and cooperative reflection. It was discovered that the ramifications of reflective teaching go beyond merely improving teaching efficacy to encouraging professional advancement, cultivating a culture of constant enhancement, and bolstering ethical teaching practices. The study emphasizes the importance of incorporating reflective practices into teacher professional development, nurturing a reflective atmosphere within schools, and establishing supportive policy structures. While the research provides valuable perspectives on reflective teaching in Vietnam, it also highlights areas requiring further exploration, such as extending the research to rural scenarios and utilizing diverse data gathering techniques.
Keywords: On-action reflection; reflective teaching; teacher professional development; Vietnam